STUDY OF PHRASEOLOGICAL UNITS IN UZBEK LINGUISTICS - Nishonova Adiba Adkhamjon's Qizi (Scholar Express Journal, 2024)
Phraseological units are a layer that embodies the national and cultural characteristics of the people. A large-scale study of such a language helps to better understand the national mentality and views of existence of the nation that owns that language. This article talks about the study of phraseological knowledge in world and Uzbek linguistics.
Keywords: Phraseology; Phraseme; Valence